Reliable control of stochastic systems via sliding mode technique. (14th September 2012) - Niu, Yugang; Liu, Yonghui; Jia, Tinggang
SUMMARY: This paper considers the problem of sliding mode control for uncertain stochastic systems with possible occurrence of actuator faults. There exist parameter uncertainties and state‐dependent noise. Moreover, the faults may happen in any of the actuators. The reliable designing on both passive and adaptive sliding mode controllers is investigated, respectively. Both the reachability of the specified sliding surface and the stochastic stability of the sliding motion are analyzed using the stochastic Lyapunov theory. Finally, numerical simulation results are given.Copyright © 2012 John Wiley & Sons, Ltd.